Continuation or Evolution? Changes in Pottery Production and Vessel Types Used in Pomerelian (Gdańsk Pomerania) Towns in the Early-Modern Period - Starski, Michał (Institute of Archaeology and Ethnology Polish Academy of Sciences, 2021)
The article discusses changes in production and the of the pottery used in towns in Pomerelia in the early-modern period. These considerations are based on advanced research on late-medieval pottery-making of the region and the relatively poorer state of knowledge about the continuity of transformations at the beginning of the early-modern period. The vantage point for this study is a characterisation of the source base, including both the artefactual and written evidence. This enables the tracing of changes, and characteristic features of goods used, in the 16th century
ill. ; 24 cm
Keywords: ceramics; pottery; Pomerelia; Gdańsk Pomerania; early-modern; towns